Hispanisms and Homosexualities - Irwin, Robert McKee, 1962-; Molloy, Sylvia, 1938-2002 (Book collections on Project MUSE., 1998)
A man masquerading as a lesbian in Spain's Golden Age fiction. A hermaphrodite's encounters with the Spanish Inquisition. Debates about virility in the national literature of postrevolutionary Mexico. The work of contemporary artists Reinaldo Arenas, Severo Sarduy, and María Luisa Bemberg. The public persona of Pedro Zamora, former star of MTV's The Real World. Despite an enduring queer presence in Hispanic literatures and cultures, most scholars have avoided the specter of sexual dissidence in the Spanish-speaking world. In Hispanisms and Homosexualities, editors Sylvia Molloy and Robert Irwin bring together a group of essays that advance Hispanic studies and gay and lesbian studies by calling into question what is meant by the words Hispanic and homosexual. The fourteen contributors to this volume not only offer queer readings of Spanish and Latin American texts and performances, they also undermine a univocal sense of homosexual identities and practices. Taking on formations of national identity and sexuality; the politics of visibility and outing; the intersections of race, sexuality, and imperial discourse; the status of transvestism and posing; and a postmodern aesthetic of camp and kitsch, these essays from both established and emerging scholars provide a more complex and nuanced view of related issues involving nationality, ethnicity, and sexuality in the Hispanic world. Hispanisms and Homosexualities offers the most sophisticated critical and theoretical work to date in Hispanic and queer studies. It will be an essential text for all those engaged with the complexities of ethnic, cultural, and sexual subjectivities. Contributors. Daniel Balderston, Emilie Bergmann, Israel Burshatin, Brad Epps, Mary S. Gossy, Robert Irwin, Agnes I. Lugo-Ortiz, Sylvia Molloy, Oscar Montero, Jose Esteban Muñoz, Jose Quiroga, Ruben Ríos Avila, B. Sifuentes Jáuregui, Paul Julian Smith.